2014
DOI: 10.1158/0008-5472.can-13-2775
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Lung Cancer Gene Expression Identifies PTK7 as a Survival Gene in Lung Adenocarcinoma

Abstract: Lung cancer remains the most common cause of cancer-related death worldwide and it continues to lack effective treatment. The increasingly large and diverse public databases of lung cancer gene expression constitute a rich source of candidate oncogenic drivers and therapeutic targets. To define novel targets for lung adenocarcinoma (ADC), we conducted a large scale meta-analysis of genes specifically overexpressed in ADC. We identified an eleven-gene signature that was overexpressed consistently in ADC specime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 52 publications
3
117
0
Order By: Relevance
“…We and others have shown that knockdown of PTK7 decreases proliferation, survival, wound healing, and invasion of esophageal squamous cell carcinoma cells [20] and reduces cell viability and tumor burden in lung adenocarcinoma [31], demonstrating oncogenic roles for PTK7. In contrast, we also noted a tumor-suppressive role of PTK7, as overexpression of PTK7 decreased cell proliferation, invasion, and migration in lung squamous cell carcinoma [32].…”
Section: Discussionmentioning
confidence: 70%
“…We and others have shown that knockdown of PTK7 decreases proliferation, survival, wound healing, and invasion of esophageal squamous cell carcinoma cells [20] and reduces cell viability and tumor burden in lung adenocarcinoma [31], demonstrating oncogenic roles for PTK7. In contrast, we also noted a tumor-suppressive role of PTK7, as overexpression of PTK7 decreased cell proliferation, invasion, and migration in lung squamous cell carcinoma [32].…”
Section: Discussionmentioning
confidence: 70%
“…AXL is a RTK that promotes OVCA metastasis (56). ACTA2 (alpha smooth muscle actin) drives metastasis and poor prognostis in lung cancer (57). ADRA2A (adrenoreceptor alpha 2A), stimulates proliferation and is associated with MAPK activation (58).…”
Section: Discussionmentioning
confidence: 99%
“…We have repeatedly demonstrated the utility of this approach in identifying novel drug targets, diagnostic and prognostic biomarkers, and repurposing FDA-approved drugs in a broad spectrum of diseases including organ transplant, cancer, sepsis, and bacterial and viral infections (14)(15)(16)(17)(18)(19)(20)(21). Here, we applied our multicohort analytical method to 2 SSc gene expression datasets, obtained from 158 skin biopsies from SSc patients, referred to as the UCSF1 cohort (GSE9285) (11) and the Boston cohort (GSE32413) (10) to identify a 415-gene signature.…”
Section: Introductionmentioning
confidence: 99%